A New Route for Dioxygen Activation Uncovered from Quantum Mechanics Investigations of X‐Ray‐Diffraction‐Captured Intermediates of the Ferroxidase Reaction of Ferritins from Gram‐Negative Bacteria. Issue 4 (25th February 2020) - Pietra, Francesco
Abstract: Following the recent reassessment from X‐ray‐diffraction‐caught short‐path uptake to wide permeation of the S20A mutant Escherichia coli ferritin by ferrous ions, what happens when dioxygen gets to the diiron system is investigated. It is shown that the previously X‐ray‐caught situation of an unbound‐dioxygen diferrous state actually is an ephemeral state that changes into a P‐type peroxodiferric state, while a water molecule moves to bridge the two ferric ions, in what appears to be a remarkable redox process. All this stems from density functional theory (DFT)‐based quantum mechanics‐molecular mechanics and broken symmetry (BS) calculations that are extended to X‐ray‐diffraction‐caught oxodiferric and I‐type peroxodiferric systems from other subunits of the same crystal structure, validating them while determining antiferromagnetic coupling with all such diiron systems except the oxodiferric one. The latter converged, on BS, to ferromagnetic coupling under a wide variety of hybrid DFT functionals and basis sets. The trend of the Heisenberg J coupling reflects and substantiates the structures of the diiron core. Abstract : A stereoview of the rare P‐type peroxodiferric intermediate, characterized by antiferromagnetic coupling, formed during quantum mechanics‐molecular mechanics on a model of the X‐ray‐caught unbound dioxygen intermediate is presented. This represents a new route to dioxygen activation by ferritins of Gram‐negative bacteria, and affords quantum mechanics validation to the previously X‐ray‐caught I‐type peroxodiferric and oxodiferric intermediates from the same ferritins.